Crossroads of the Classroom: Narrative Intersections of Teacher Knowledge and Subject Matter - Ross, Vicki; Chan, Elaine; Keyes, Dixie (Advances in research on teaching, 2017)
This book aims to explore and make visible the intersection of subject matter knowledge and teacher knowledge in the narratives of teachers. This complicated interaction between these two bodies of knowledge is often studied and little understood.  This book uses narrative to examine the complexities of teaching and learning. The authors of the chapters, as well as the editors, use innovative approaches to narrative methodology for research on teaching and teacher education in areas of education critical to teachers' lives. Particularly through this book, they continue to advance the work of researchers to display narratives of educator lives and ways of knowing while opening the space for a community of narrative scholars.